Identification, cultivation condition of Parasevetibacter sp C101 and antimicrobial activity of the bacterial culture extract - Tuan, Nguyen Manh; Quang Vien, Le; Phuc Hung, Truong; Minh Quan, Tran; Hien, Do Thi; Bich Due, Do; Khuyen, Duong Thi (Vietnam Journal of Biotechnology, 2022)
During the recent decade, uncultured bacteria have been special interest as potential candidates for discovering novel antibacterial compounds. Two strains C101 and C102 were negative Gram bacteria, only growing on low nutrient media as R2A/3, NB/3, LB/10 and R4/10 compared to the usual. On R2A/3 medium, colonies of the isolates were round, convex, lemon yellow color with the size of 1-1.5 mm after six days of incubation at 28oC. Cells were 0.2-0.3 × 0.8-1.3 µm. The strains C101 and C102 were able to grow at temperature ranging 15-37oC (optimum at 25-28oC), pH 5-8 (optimum in pH 6-7). The sequences of 16S rRNA genes from strain C101 (MT756087) and C102 (MT756088) shared 100% identity. Analysis of full-length 16S rRNA gene sequence of strain C101 via using NCBI Blast, EzTaxon Database revealed the highest similarity of 99.18-100% to uncultured clones, and 97.86% to type species as Parasegetibacter terrae SGM2-10T. Genetic sequence analysis data showed that strain C101 should be considered a novel candidate species of the genus Parasegetibacter. Antibacterial compound was extracted from culture of strain C101 in R4/10 medium for ten days of shaking incubator at 28oC and exhibited susceptible activity to inhibit Bacillus anthracis KEMB 211-146 at a concentration of 2 µg/L and Staphylococcus aureus ATCC 6538 at 4 µg/L; intermediate inhibiting Bacillus subtilis KEMB 51201-001 at 8 µg/L, Staphylococcus epidermidis ATCC 14990 at 8 µg/L, and S. aureus CCARM 3155 at 16 µg/L; inhibition of S. aureus CCARM 3095 at 64 µg/L, S. aureus CCARM 3192 at 32 µg/L, and S. epidermidis CCARM 3710 at 64 µg/L.